2018
DOI: 10.1021/acssuschemeng.8b04025
|View full text |Cite
|
Sign up to set email alerts
|

Citrus limetta Organic Waste Recycled Carbon Nanolights: Photoelectro Catalytic, Sensing, and Biomedical Applications

Abstract: The present work reports green route-waste recycled carbon nanolights, i.e., carbon dots (GCDs), synthesized via a facile one-step pyrolysis method from Citrus limetta waste pulp. The size of these obtained pristine GCDs is ∼4−7 nm (HR-TEM), with high optical and structural quality as revealed by FT-IR and Raman spectroscopic analysis. They exhibit the highest quantum yield of 63.3% over other similar green synthesized GCDs, favorable for many applications. Further, we demonstrate the multifunctional aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…Alternatives such as photothermal therapies have promise but do not share the spatial resolution possible with APDT [ 20 ]. Accordingly, an emphasis has been placed on optimizing the properties of photosensitizing molecules for antimicrobial applications, particularly in tuning the photophysical properties of those agents [ 21 ] for maximized ROS quantum yields [ 22 , 23 ]. By optimizing these characteristics, it is possible to improve the efficiency of light utilization by the photosensitizer, and even to select for activation wavelengths that are themselves not inherently harmful, unlike short-wavelength ultraviolet light (UV-C) [ 24 ].…”
Section: Introduction: Photodynamic Antimicrobial Therapy and Carbmentioning
confidence: 99%
“…Alternatives such as photothermal therapies have promise but do not share the spatial resolution possible with APDT [ 20 ]. Accordingly, an emphasis has been placed on optimizing the properties of photosensitizing molecules for antimicrobial applications, particularly in tuning the photophysical properties of those agents [ 21 ] for maximized ROS quantum yields [ 22 , 23 ]. By optimizing these characteristics, it is possible to improve the efficiency of light utilization by the photosensitizer, and even to select for activation wavelengths that are themselves not inherently harmful, unlike short-wavelength ultraviolet light (UV-C) [ 24 ].…”
Section: Introduction: Photodynamic Antimicrobial Therapy and Carbmentioning
confidence: 99%
“…In the full‐scan spectrum (Figure a), signals of C 1s and O 1s are discernible at 284 and 532 eV, with atomic ratio of 71.11% and 28.89%, respectively. The C 1s spectrum (Figure b) presents three carbon species of C−C/C=C at 284.5 eV, C−O at 286.8 eV, and C=O at 290.1 eV . The O 1s spectrum (Figure c) can be deconvoluted into two oxygen components at 531.7 and 533.0 eV, being associated with C=O and C−O, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Carbon dots (CDs), as a fascinating class of nanocarbons, have provoked widespread interest in various fields ranging from bioimaging and sensors to photovoltaics and catalysis, because of their alluring optical properties, excellent biocompatibility, high stability and facile functionalization . The past several years have seen the emergence of numerous synthetic strategies to prepare CDs using diverse precursors, including graphene, carbon nanotubes, aromatic molecules, saccharides, amino acids, citric acid, frying oil, combustion soot, plastics, biomass, and so on. With a view to reducing cost, saving resources, and protecting the environment, the reuse of man‐made wastes, such as frying oil, combustion soot, and plastics, as the initial sources toward CDs is more preferable.…”
Section: Introductionmentioning
confidence: 99%
“…CQDs were synthesized using the waste pulp of Citrus limetta as a green carbon precursor. 44 The present nding reveals a more accessible one-step synthesis methodology for the synthesis of water-soluble waste-derived plasmonic nanostructures. Au-CQDs were synthesized by the continuous stirring of the HAuCl 4 (used as a precursor) (1 mM) and CQD (0.5 M) solution in the ratio of 1 : 9 at room temperature under visible light irradiation for a duration of 20 minutes.…”
Section: Synthesis P Au/ag -Cqd/tio 2 Nanobersmentioning
confidence: 93%
“…23 Owing to the visible light absorption, the up-conversion and electron-donating property of CQDs, and the photocatalytic activity of the CQDanchored TiO 2 composites has been revealed to enhance in the reported literature. [29][30][31][32] Besides, plasmonic nanostructures are widely utilized as active sensitizers for visible light; however, they are mainly derived from a synthetic route. Similarly, in the recent past, Agloaded zinc/aluminium-layered double hydroxide nanocomposites, Ag/AgIn 5 S 8 nanoparticles and BiOCl/AgCl/BiVO 4 photocatalysts have been investigated for the photocatalytic degradation of pharmaceutical drugs, and the results showed that their enhanced photocatalytic activity is attributed to the boosted surface plasmon resonance (SPR) effect of Ag nanostructures.…”
Section: A Introductionmentioning
confidence: 99%